RP-US relations a historical perspective [videorecording] (Quezon City ABS-CBN News and Public Affairs, 1990)
Relationship and the roots of friendship between the United States and the Philippines; The rejection of the Senate on the bases agreement; and An exclusive interview with Senate President Jovita Salonga.
RP-US relations ; a historical perspective / producer Veronica Pedrosa (10 min.) -- RP-US relations : on the bases of friendshipn / producer, Vivian Zalvidea (15 min.) -- One on one interview with Senate President Jovito Salonga / producer, Loren Legarda, Joey Flora (20 min.)
VHS.
Keywords: Salonga, Jovito R; Military bases, American -- Philippines; Philippines -- Foreign relations -- United States; United States -- Foreign relations -- Philippines